Integrated Curriculum Management in Integrated Undergraduate Programs - Didi Maslan; Afrahul Fadhila Daulai; Sapri (Ta'dib, 2023)
This research aims to analyze program factors, implementation, evaluation and barriers to curriculum integration between Ma'had Abu Ubaidah bin Al-Jarrah and the Faculty of Islamic Religion (FAI) Muhammadiyah University of North Sumatra (UMSU) in the Integrated Undergraduate Program. This research method uses a qualitative approach with a descriptive type. Data collection techniques include interviews, observation and documentation studies. Data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions. Research findings show; 1) The curriculum integration program between Ma'had Abu Ubaidah bin Al-Jarrah and FAI UMSU in the Integrated Undergraduate Program is a strategic collaboration to provide service diplomas to students, as well as facilitate students to continue higher education and improve the quality of Islamic education. 2) Implementation of curriculum integration between Ma'had Abu Ubaidah bin Al-Jarrah and FAI UMSU in the Integrated Undergraduate Program is carried out through three aspects, namely integration of lecture schedules, integration of courses, and integration of assessments. 3) Evaluation of curriculum integration between Ma'had Abu Ubaidah bin Al-Jarrah and FAI UMSU in the Integrated Undergraduate Program is carried out every semester. This program is able to provide positive impacts such as stability in student numbers, increasing student interest in learning, increasing the number of students with various abilities. 4) Obstacles in implementing curriculum integration between Ma'had Abu Ubaidah bin Al-Jarrah include; lack of communication and coordination, time and cost constraints, delays and division of focus, curriculum changes, and students' perceptions of the value of knowledge.